Algorithm of development of medico-technological standard operational procedures in the course of introduction of strategic management of the medical organization - I. G. Samoylova (Журнал инфектологии)
Questions of introduction of the standard operational procedures (SOP) in medical practice and quality management of healthcare institutions are considered. Communication of SOP with standards and orders of rendering medical care in the Hospitals of children Infections is shown.The algorithm of development of SOP in the conditions of standardization of medical care is offered. Value of SOP in the course of controlling use at introduction of strategic management of the medical organization is shown.